Chinese version of Dominic Interactive – A self-report video game for assessing mental health in young children - Kovess-Masfety, Viviane; Yan, Guoli; Yin, Huifang; Sun, Ling; Hou, Xiaofei; Li, Minghui; Li, Peiyao; Su, Xuyang; Phillips, Michael R.; Xu, Guangming (Frontiers in Psychiatry, 2023)
Objectives Assess the validity of the Chinese version of the Dominic Interactive (DI), a 91-item, video-based diagnostic screening instrument for children that assesses four internalized disorders (phobias, separation anxiety disorder, generalized anxiety disorder, and major depressive disorder) and three externalized disorders (attention-deficit/hyperactivity disorder, conduct disorder, oppositional defiant disorder). Methods (1) Compare DI-generated “probable” or “possible” diagnoses to diagnoses based on the Development and Well-Being Assessment (DAWBA) instrument in 113 psychiatric outpatients and 20 community controls. (2) Administer DI to 1,479 children from elementary schools in Tianjin. Results In the validation sample, DI with DAWBA concordance was much greater for internalized disorders (mean Kappa = 0.56) than for externalized disorders (mean kappa = 0.11). The positive predictive value of DI diagnoses ranged from 0.96 (generalized anxiety disorder) to 25% (oppositional defiant disorder) and negative from 0.81 to 0.96. Using “probable” cuts provides better results. In the survey, prevalence of probable DI disorders ranged from 1.0% (conduct disorder) to 13.1% (phobias). Internal consistency of all DI items was excellent (Cronbach alpha = 0.93) and that of the seven subscales ranged from 0.64 (phobias) to 0.87 (major depressive disorder). In multilevel SEM analyses, SRMR (Standardized root mean square residual) or each of the seven diagnoses was below 0.08 and each coefficient of determination was below 0.60. Conclusion The Chinese DI is a convenient method of screening common mental disorders in Chinese children mainly for internalized disorders, which are the most prevalent diagnoses in that population. However its high negative predictive values for externalized could be used for screening.